Cost and cost-effectiveness of a real-world HCV treatment program among HIV-infected individuals in Myanmar. Issue 2 (24th February 2021) - Marquez, Lara K; Chaillon, Antoine; Soe, Kyi Pyar; Johnson, Derek C; Zosso, Jean-Marc; Incerti, Andrea; Loarec, Anne; Nguyen, Aude; Walker, Josephine G; Mafirakureva, Nyashadzaishe; Lo Re III, Vincent; Wynn, Adriane; et al.
Abstract : Introduction: Over half of those hepatitis C virus (HCV)/HIV coinfected live in low-income and middle-income countries, and many remain undiagnosed or untreated. In 2016, Médecins Sans Frontières (MSF) established a direct-acting antiviral (DAA) treatment programme for people HCV/HIV coinfected in Myanmar. The purpose of our study was to evaluate the real-world cost and cost-effectiveness of this programme, and potential cost-effectiveness if implemented by the Ministry of Health (MoH). Methods: Costs (patient-level microcosting) and treatment outcomes were collected from the MSF prospective cohort study in Dawei, Myanmar. A Markov model was used to assess cost-effectiveness of the programme compared with no HCV treatment from a health provider perspective. Estimated lifetime and healthcare costs (in 2017 US) and health outcomes (in disability-adjusted life-years (DALYs)) were simulated to calculate the incremental cost-effectiveness ratio (ICER), compared with a willingness-to-pay threshold of per capita Gross Domestic Product in Myanmar (1250). We evaluated cost-effectiveness with updated quality-assured generic DAA prices and potential cost-effectiveness of a proposed simplified treatment protocol with updated DAA prices if implemented by the MoH. Results: From November 2016 to October 2017, 122 with HIV/HCV-coinfected patients were treated with DAAs (46% with cirrhosis), 96% (n=117) achieved sustained virological response. Mean treatment costs were 1229 (without cirrhosis) and 1971 (with cirrhosis), with DAA drugs being the largest contributor to cost. Compared with no treatment, the program was cost-effective (ICER 634/DALY averted); more so with updated prices for quality-assured generic DAAs (ICER 488/DALY averted). A simplified treatment protocol delivered by the MoH could be cost-effective if associated with similar outcomes (ICER 316/DALY averted). Conclusions: Using MSF programme data, the DAA treatment programme for HCV among HIV-coinfected individuals is cost-effective in Myanmar, and even more so with updated DAA prices. A simplified treatment protocol could enhance cost-effectiveness if further rollout demonstrates it is not associated with worse treatment outcomes.